Current challenges in understanding and forecasting stable boundary layers over land and ice - Steeneveld, Gert-Jan (Frontiers in Environmental Science, 2014)
Understanding and prediction of the stable atmospheric boundary layer is challenging. Many physical processes come into play in the stable boundary layer, i.e. turbulence, radiation, land surface coupling and heterogeneity, orographic turbulent and gravity wave drag. The development of robust stable boundary-layer parameterizations for weather and climate models is difficult because of the multiplicity of processes and their complex interactions. As a result, these models suffer from biases in key variables, such as the 2-m temperature, boundary-layer depth and wind speed. This short paper briefly summarizes the state-of-the-art of stable boundary layer research, and highlights physical processes that received only limited attention so far, in particular orographically-induced gravity wave drag, longwave radiation divergence, and the land-atmosphere coupling over a snow-covered surface. Finally, a conceptual framework with relevant processes and particularly their interactions is proposed.